Differential and selective medium for isolation of Yersinia enterocolitica from stools. - Agbonlahor, D E (1982)
A new differential and selective medium, DYS agar, was developed and evaluated from the isolation of Yersinia enterocolitica. Ther bile salts content of the medium resulted in high selectivity, and inclusion of arabinose, lysine, and arginine rendered Y. Enterocolitica very distinct from Proteus spp., Pseudomonas spp., and other members of the family Enterobacteriaceae. DYS medium was more efficient for the isolation of Y. enterocolitica from experimentally inoculated fecal specimens than MacConkey, deoxycholate-citrate, and salmonella-shigella agars. Although the medium showed selectivity similar to that of another relatively new medium. Y medium (a selective medium for Y. enterocolitica containing sodium oxalate). DYS agar was found to be superior to Y medium in terms of differentiation of Y. enterocolitica from other intestinal organisms. DYS medium is simple to prepare.